Family and Home as Elements of Worldview in Adults from Full and One-Parent Families - Baruk-Dzięcioł, Ewa Beata (Studia Warmińskie, 2019)
The family and the space of the family home play a key role in every individual’s life, both in the personal and social dimension. This leads to the question of whether the type of the family of origin may model the view of the family environment, which is generated in the consciousness of adults. The answer to this question may lie in the results of empirical studies conducted by means of an association experiment, which is one of the instruments for diagnosing the image of the world in the consciousness, expressed through the language of the people participating in the experiment. The analysis of the lexical material generated in association with the key words family and home highlighted certain characteristics of their image among respondents originating from various types of families. These characteristics are particularly noticeable in two aspects. The first is a similar range of the semantic associations generating the prototype image of home and family; the second is the different frequencies of use within the particular verbal reactions of the study participants. To conclude, it is evident that family and home are elements of the worldview in adults whose profile is heavily determined by culture. However, the experience of the family of origin seems to model the manner in which the respondents perceive the importance of particular aspects of this image.